Cellulitis-related Rhodococcus equi in a cat harboring VAPA-type plasmid pattern - Rocha, Brizza Zorayd Luz Lopes; Portilho, Fábio Vinícius Ramos [UNESP]; Garino Júnior, Felício; Monti, Fabiana dos Santos; de Almeida, Beatriz Oliveira [UNESP]; de Souza, Adriana Aparecida Lopes [UNESP]; Morizane, Yuri; Sakaizawa, Naho; Suzuki, Yasunori; Kakuda, Tsutomu; Takai, Shinji; de Farias, Marconi Rodrigues; et al. (Elsevier, 2021)
Rhodococcus equi is a well-known intracellular facultative bacterium that is opportunistic in nature, and a contagious disease-causing agent of pyogranulomatous infections in humans and multihost animals. Feline rhodococcosis is an uncommon or unnoticed clinical condition, in which the organism is usually refractory to conventional antimicrobial therapy. The pathogenicity of the agent is intimately associated with plasmid-governed infectivity, which is attributed to the presence of plasmid-encoded virulence-associated proteins (Vap). Three host-adapted virulence plasmid types (VAPs) have been distinguished to date: pVAPA, pVAPB, and pVAPN, whose infections are related to equine, pig, and bovine or caprine origin, respectively, while humans are infected by all three VAP types. Most virulence studies with R. equi plasmid types in animals involve livestock species. Conversely, data on the pathogenicity and human relevance of the virulence plasmid profile of R. equi isolated from cats remains unclear. This report describes a case of cellulitis-related R. equi that harbors the pVAPA-type in a cat with cutaneous lesion. Long-term therapy of the cat using marbofloxacin, a broad-spectrum third-generation fluoroquinolone, resulted effectiveness. pVAPA is a host-adapted virulent type that has been associated predominantly with pulmonary foal infections. Our cat had a history of contact with other cats, livestock (including horses), and farm environment that could have favored the transmission of the pathogen. Besides no clear evidence of cat-to-humans transmission of the pathogen, the identification of R. equi harboring pVAPA-type in a cat with cutaneous abscessed lesion represent relevance in human health because this virulent type has been described in people worldwide with clinical rhodococcal disorders.
Keywords: Extrapulmonary signs; Feline rhodococcosis; MALDI-TOF MS; Pathogenicity; pVAPA-type; Virulence plasmid profile